Exploratory investigation of grouted bar-in-duct connections under direct tensile load. (20th September 2018) - Elsayed, M.; Nehdi, M.L.; Provost-Smith, D.J.; Eissa, O.S.
Highlights: Bond behaviour of grouted connections under monotonic tensile loading was explored on 22 full-size specimens. Grouted connections behave quite differently from bar-in-concrete model assumed in design codes. Varying embedment length did not affect bond stress and slip, but influenced failure mechanism of connections. Model was calibrated and accurately predicted experimental results. Enhanced understanding of behaviour of connections acquired, showing need for revisions in relevant design code provisions. Abstract: Grouted dowel connections are widely used to resist tension induced by in-plane straining actions and to provide ductility to precast concrete load bearing wall structures. Yet, such connections have not yet been duly investigated. Current design code and standard provisions treat it similar to a simple bar-in-concrete detail. The present study reports the findings of 22 full-scale tests undertaken to examine the bond behaviour of grouted connections under monotonic tensile loading. The examined test parameters included the bar embedment length, bar material and corrugated duct. Results indicate that grouted connections behave quite differently from the bar-in-concrete model assumed in design codes, primarily due to the confinement mechanism of the duct, which provides restraint to lateral expansion of the grout. Varying the embedment length seemed to affect both the bond stress and slip, but did not influence the failure mechanism of the connections. The experimental results were used to calibrate two well-known bond-slip analytical treatments, predictions of which appear to be in good agreement with experimental results. The experimental and analytical findings provide an enhanced understanding on the behaviour of such connections, highlighting the need for revisions in future relevant design code provisions.